Effects and mechanisms of 6-hydroxykaempferol 3,6-di-O-glucoside-7-O-glucuronide from Safflower on endothelial injury in vitro and on thrombosis in vivo - Wang, Li-Wei; He, Jiang-Feng; Xu, Hai-Yan; Zhao, Peng-Fei; Zhao, Jie; Zhuang, Cong-Cong; Ma, Jian-Nan; Ma, Chao-Mei; Liu, Yong-Bin (Frontiers in Pharmacology, 2022)
ABSTRACT Background: The florets of Carthamus tinctorius L. (Safflower) is an important traditional medicine for promoting blood circulation and removing blood stasis. However, its bioactive compounds and mechanism of action need further clarification. Objective: This study aims to investigate the effect and possible mechanism of 6-hydroxykaempferol 3,6-di-O-glucoside-7-O-glucuronide (HGG) from Safflower on endothelial injury in vitro, and to verify its anti-thrombotic activity in vivo. Methods: The endothelial injury on human umbilical vein endothelial cells (HUVECs) was induced by oxygen-glucose deprivation followed by reoxygenation (OGD/R). The effect of HGG on the proliferation of HUVECs under OGD/R was evaluated by MTT, LDH release, Hoechst-33342 staining, and Annexin V-FITC apoptosis assay. RNA-seq, RT-qPCR, Enzyme-linked immunosorbent assay and Western blot experiments were performed to uncover the molecular mechanism. The anti-thrombotic effect of HGG in vivo was evaluated using phenylhydrazine (PHZ)-induced zebrafish thrombosis model. Results: HGG significantly protected OGD/R induced endothelial injury, and decreased HUVECs apoptosis by regulating expressions of hypoxia inducible factor-1 alpha (HIF-1α) and nuclear factor kappa B (NF-κB) at both transcriptome and protein levels. Moreover, HGG reversed the mRNA expression of pro-inflammatory cytokines including IL-1β, IL-6, and TNF-α, and reduced the release of IL-6 after OGD/R. In addition, HGG exhibited protective effects against PHZ-induced zebrafish thrombosis and improved blood circulation. Conclusion: HGG regulates the expression of HIF-1α and NF-κB, protects OGD/R induced endothelial dysfunction in vitro and has anti-thrombotic activity in PHZ-induced thrombosis in vivo.